Spectral Characterization and Antibacterial Activities of Benzyloxybenzaldehydethiosemicarbazone, 3,4-Dihydroxybenzaldehydeisonicotinoylhydrazone and their Transitional Metal Complexes - Lakshmi Narayana Suvarapu; A. Varada Reddy; G. Satheesh Kumar; Sung Ok Baek (E-Journal of Chemistry)
The synthesis and spectral characterization of benzyloxy-benzaldehydethiosemicarbazone (BBTSC) and the study of antibacterial activity of ligands BBTSC, 3,4-dihydroxybenzaldehydeisoni- cotinoylhydrazone (3,4-DHBINH) and their transition metal complexes was studied. The composition of the metal complexes was also evaluated by using Job’s method, molar-ratio method and Asmus’ method. The antibacterial activities of BBTSC, 3,4-DHBINH and their complexes i.e., Cu(II)-BBTSC, Pd(II)-BBTSC, Cr(VI)- 3,4-DHBINH, Ti(IV)- 3,4-DHBINH and Pd(II)-3,4-DHBINH were studied against two gram positive bacteria and two gram negative bacteria. Antibacterial activities were evaluated by agar cup well method with the help of Luria Bertoni plates.